Microbiological evaluation of infected wounds of the extremities in 214 adults. Issue 1 (1st January 1999) - Holzapfel, L; Jacquet-Francillon, T; Rahmani, J; Achard, P; Marcellin, E; Joffre, T; Lallement, P Y; Bousquet, A; Devaux, S; Coupry, A
Abstract : OBJECTIVE: The aim of this multicentre prospective study was to analyse microbial pathogens cultured from an infected wound. METHODS: The study was performed in the emergency rooms of 10 public hospitals. All adult patients with a clinical diagnosis of cellulitis after a wound in the upper or lower extremities were included. Cultures were obtained with swabs from infected lesions. Micro-organisms cultured were identified by the usual methods and susceptibility testing was performed. RESULTS: The study population consisted of 214 patients, 153 men and 61 women, with a mean (SD) age of 40 (10) years. Wound cultures remained sterile in 28 cases and infected with micro-organisms in 186 cases. Of the 186 positive cultures, three were not identified. Of the 183 remaining cultures, one micro-organism was present in 132 patients (62%) and several micro-organisms in 51 patients (24%). A total of 248 micro-organisms were isolated in 183 patients. Staphylococcus and streptococcus were the most frequently isolated micro-organisms (56% and 21% respectively) followed by Gram negative bacilli (18%). Determination of the susceptibility to the antibiotics commonly used to treat wound infections showed resistance in some cases. CONCLUSION: These results support the need always to take culture specimens from infected wounds for microbiological evaluation and antibiotic susceptibility determination, so that adapted chemotherapy can be prescribed.